A realist evaluation of loneliness interventions for older people. (27th September 2021) - Day, Alice; Phelps, Kay; Maltby, John; Palmer, Emma; Snell, Keith; Raine, Derek; Conroy, Simon
Abstract: Introduction: the aim of this study was to develop a programme theory to inform the design of loneliness interventions and guide any future evaluations. Methods: we undertook a mixed-method evaluation, informed by the realist approach, of different approaches to loneliness in one health and social care system in the East Midlands, UK. We used a combination of documentary analysis, interviews/focus groups with service providers and users and quantitative analysis to develop an initial programme theory. Results: common aims of local interventions included enhancing social connectivity, providing emotional support and advice/information; recurring interventions included social activities, emotional support, advice and information, lunch clubs, learning new skills and practical support. None were robustly evaluated. Fifty-six service user or providers were involved in interviews or focus groups, which highlighted the causes of loneliness, preferred services, access to services, thoughts about intervention configuration and desired outcomes from services. The themes emerging from the interviews/focus groups from both service provider and service user perspectives were combined with all of the previous emerging data to create an overarching programme theory. Statements were constructed to allow service providers to think about which interventions might be useful to achieve specific outcomes in different contexts. Conclusion: the causes and consequences of loneliness vary widely between individuals, so a personalised approach is required to identify the causes and potential solutions. This study provides some high-level principles that can help commissioners and providers to tailor interventions to the individual needs of service users.